VD_FINDINFO Faillite / 2009 / 16 vom 23. Juni 2009 - VD Tribunal cantonal (2009)
FAILLITE SANS POURSUITE PRÉALABLE, INSOLVABILITÉ, ACTE DE DÉFAUT DE BIENS | 174 al. 1 LP, 174 al. 2 LP, 190 al. 1 ch. 2 LP, 194 LP